Sustainability Impact: A Representation of Social Enterprise Value - Anisa Kusumawardani; Fibriyani Nur Khairin; Ginting, Yoremia Lestari (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2024)
Social enterprises have a unique characteristic in their business objectives, which is the element of profit as well as creating value that addresses social issues in society. In practice, the sustainability impact represents the value that shows how social enterprises establish strategies, conduct daily operations, and build partnerships with stakeholders. Therefore, this study aims to explore and understand the meaning of